INOVASI PENDIDIKAN ISLAM DI AL-IRSYAD - Aulia Aulia; Zulpan Harahap; Abdul Khalil (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This research is intended to explore the implementation of education at IslamicInstitution ofAl Irsyad. This research focus on what innovation that this Islamicorganization applied in their schools. This research used library and field method.The data were collected by using documentation study and deep interview witheducational staffs. The results of this research revealed that this Islamic Educationused many kinds of books not only use Islamic books but also general books. TheSchools still maintained their identity as Islamic Organization but they also usedmodern education to fulfill the advance of educational.